2022
DOI: 10.3389/fphy.2022.875574
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Behavioral Characteristics and Diffusion Mechanisms: A Comparative Analysis Based on Social Bots and Human Users

Abstract: In the field of social media, the systematic impact that bot users bring to the dissemination of public opinion has been a key concern of the research. To achieve more effective opinion management, it is important to understand how and why behavior differs between bot users and human users. The study compares the differences in behavioral characteristics and diffusion mechanisms between bot users and human users during public opinion dissemination, using public health emergencies as the research target, and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…The rapid development of LLMs provides opportunities to create more realistic contributions to discourse (Park et al 2023). Recent studies have found that LLMs can generate arguments (Palmer and Spirling 2023), draw on contextual knowledge (Törnberg 2023), or perform AAAI Spring Symposium Series (SSS-24) basic reasoning tasks (Bubeck et al 2023). There are questions regarding what happens if a user communicates with a bot on a social media platform without realizing it is not human, as well as if the LLMs can manipulate the information propagation and digital discourse.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of LLMs provides opportunities to create more realistic contributions to discourse (Park et al 2023). Recent studies have found that LLMs can generate arguments (Palmer and Spirling 2023), draw on contextual knowledge (Törnberg 2023), or perform AAAI Spring Symposium Series (SSS-24) basic reasoning tasks (Bubeck et al 2023). There are questions regarding what happens if a user communicates with a bot on a social media platform without realizing it is not human, as well as if the LLMs can manipulate the information propagation and digital discourse.…”
Section: Introductionmentioning
confidence: 99%